Considerations for the Full Global Withdrawal of Oral Polio Vaccine After Eradication of Polio. (1st July 2017) - Hampton, Lee M.; du Châtellier, Gaël Maufras; Fournier-Caruana, Jacqueline; Ottosen, Ann; Rubin, Jennifer; Menning, Lisa; Farrell, Margaret; Shendale, Stephanie; Patel, Manish
Abstract: Eliminating the risk of polio from vaccine-derived polioviruses is essential for creating a polio-free world, and eliminating that risk will require stopping use of all oral polio vaccines (OPVs) once all types of wild polioviruses have been eradicated. In many ways, the experience with the global switch from trivalent OPV (tOPV) to bivalent OPV (bOPV) can inform the eventual full global withdrawal of OPV. Significant preparation will be needed for a thorough, synchronized, and full withdrawal of OPV, and such preparation would be aided by setting a reasonably firm date for OPV withdrawal as far in advance as possible, ideally at least 24 months. A shorter lead time would provide valuable flexibility for decisions about when to stop use of OPV in the context of uncertainty about whether or not all types of wild polioviruses had been eradicated, but it might increase the cost of OPV withdrawal.